Mental testing and educational streaming in Ontario and Denmark in the early twentieth century: a comparative and transnational perspective. (4th May 2019) - Milewski, Patrice; Ydesen, Christian; Andreasen, Karen E.
ABSTRACT: This article compares and contrasts the use of mental testing and the formation of educational streaming in Denmark and Ontario during the interwar years. In this sense, the article adds nuances to the meaning of internationalism as well as contributing to our knowledge about how ideas of testing practices circulated among countries and continents. One way ideas and practices circulated was via informal networks promoted by the education traveller. Key proponents of mental testing in both Denmark and Ontario travelled to continental Europe, England, and the United States studying and observing the practices and institutional arrangements associated with educational streaming. Our main findings are that the processes used to implement mental testing in the two countries differed significantly. Mental testing was implemented much later in Denmark than in Ontario. This was due to different contextual, cultural, and historical factors that promoted changes to the existing system, or, alternatively, represented a barrier or even obstructed changes to it. Nevertheless, mental testing was implemented in both education systems as a relatively coherent technology rooted in transnational movements and exchange, but was attended by highly different practices and local meaning-making.